2020
DOI: 10.3389/fonc.2020.570080
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Assessment of Risk of Fever in Solid Tumor Patients Treated With PD-1/PD-L1 Inhibitors: A Systematic Review and Meta-Analysis

Abstract: Purpose: Drug-induced fever is frequently reported in cancer patients treated with anti-programmed cell death 1 (PD-1)/programmed cell death ligand 1 (PD-L1), and stoppage of the offending agent is the management of choice. However, given the complex management of cancer patients, this needs to be carefully studied. Therefore, we conducted a meta-analysis to estimate the risk of fever associated with anti-PD-1/PD-L1 in cancer patients. Methods: From May 2010 to 2020, an electronic search was conducted through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The PRISMA flow diagram was shown in ( Figure 1 ), while the bias assessment summary of all enrolled clinical trials were provided in ( Supplementary Figure 1 ). A total of 589 published studies was found by PubMed search, while 37 studies were gotten from the former published meta-analysis ( 61 63 ). After eligibility assessment, 5 articles were only used for the systematic review ( 13 , 20 23 ), while 42 articles were used for the final comprehensive analysis ( 4 12 , 14 19 , 24 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…The PRISMA flow diagram was shown in ( Figure 1 ), while the bias assessment summary of all enrolled clinical trials were provided in ( Supplementary Figure 1 ). A total of 589 published studies was found by PubMed search, while 37 studies were gotten from the former published meta-analysis ( 61 63 ). After eligibility assessment, 5 articles were only used for the systematic review ( 13 , 20 23 ), while 42 articles were used for the final comprehensive analysis ( 4 12 , 14 19 , 24 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…Fever, caused by a wide variety of reasons, is frequently reported in cancer patients ( 37 ), and fever is one of the most prevalent adverse events after ICIs remedy ( 7 , 8 ). When immunotherapy is combined with other therapy patterns, the incidence of fever increases remarkably.…”
Section: Etiology Of Fever Of Unknown Origin Induced By Icismentioning
confidence: 99%
“…On the basis of research into the mechanisms of immune escape, PD-1 or PD-L1 inhibitors have reshaped the therapy landscape for cancer by activating the immune system, while also gradually reporting plenty of treatment-related side effects [3]. Although the association between some adverse events and PD-1 or PD-L1 inhibitors has been extensively examined and documented [4][5][6][7][8][9], many toxicities remain unexplored, including skin toxicities [3].…”
Section: Introductionmentioning
confidence: 99%